Survei Kebutuhan Edukasi Pasien Lupus Eritematosus Sistemik - Josephine, Jennifer; Widhani, Alvina; Cahyanur, Rahmat; Karjadi, Teguh Harjono (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Patients with systemic lupus erythematosus (SLE) who suffer from chronic illness, need tailored education to better manage their condition. As nowadays education through internet and social media contributes significantly. This study aimed to assess internet usage related to lupus, educational needs, and education sources preferences among patients. Methods. This study was a cross-sectional study conducted on adult SLE patients at Allergy and Clinical Immunology Clinic, Internal Medicine Department, Cipto Mangunkusumo Hospital, Jakarta, between July-August 2023. Respondents completed a set of questionnaires regarding their internet usage related to lupus, education platform preferences, and educational needs assessment tool (ENAT). Results. Sixty-five female subjects participated, with a median (range) age of 32 (19-56) years. Respondents who used the internet and social media for lupus-related matters were 92.3%. The ENAT domains prioritized by patients were knowledge about the disease (score 89%) and emotional management (score 85%). The primary sources of education desired by patients were direct education from doctors/nurses (87.7%), Instagram (55.4%), and YouTube (55.4%). Conclusions. SLE patients expressed a strong need for knowledge about the disease and emotional management, with doctors/nurses as the preferred sources of education. The widespread use of the internet for lupus-related information indicates a great opportunity for providing education through online platforms, particularly through Instagram, and YouTube.